Productividad potencial de diferentes cruces comerciales DxP de palma africana (Elaeis guineensis Jacq.) en Coto, Costa Rica - Escóbar C, R (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
In 1969, two yield trials werw planted to compare different D x P (Dura x pisifera) commercial of oil palm (Elaeis guinecnsis Jacq). The objective of this was to evaluate diverse genetic germplasm under local conditions, and promote the reproduction of the best crosses for use as commercial planting materials. Four commercial sources werw studied: Guthries, Malaysia, Harrisons and Crosfield, Makaysia; Institut of rechreches pom les Huiles et Oleagineux Ivory Coast and Nigerian Institute for Oil Palm Research, Nigeria. One D x P cross Honduras was also included as a control. After five uears or yield recordind from the fourth year of planting, the combinatios Deli Dura x BM 119 and Deli Dura x Yangambi, showed the highest oil yield potencial for this zone. Maximum vegetative growth as shown by trunk height, length of leaf 17 and total leaf area, corresponded to the palms of crosses Deli Dura x BM 119.